Efektivitas Teknik Relaksasi Nafas Dalam Terhadap Stabilitas Emosional dan Tekanan Darah Pada Pasien Gangguan Jiwa dengan Hipertensi di Ruang Rawat Inap Rumah Sakit Ernaldi Bahar Provinsi Sumatera Selatan Tahun 2025: Penelitian - Yora Nopriani; Wufit Sauliah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Deep breathing relaxation is one of the non-pharmacological interventions that can be used to help stabilize emotions and lower blood pressure by stimulating the parasympathetic nervous system. Therefore, this study focuses on the Effectiveness of Deep Breathing Relaxation on Emotional Stability and Blood Pressure in Patients with Mental Disorders and Hypertension in the Inpatient Ward of Ernaldi Bahar Hospital, South Sumatra Province. This study employed a pre-experimental design using a one-group pretest-posttest approach. The sample was given a pretest (initial observation), followed by the intervention, and then a posttest (final observation). The Wilcoxon test results showed a significant effect on both systolic and diastolic blood pressure and emotional stability at 0.000 (p value = 0.000 < 0.05), indicating that this technique is effective in improving emotional stability and lowering blood pressure. Deep breathing relaxation can be independently practiced by patients during hospitalization or after discharge and can serve as a part of non-pharmacological nursing interventions.